Perancangan dan Pengujian Load Balancing dan Failover Menggunakan Nginx - Dani, Rahmad, Fajar Suryawan, S.T., M.Eng.Sc, Ph.D (2017)
High-traffic websites can have heavy workload on the server side, which causes a decrease in the server performance. It might also lead to system failures. A distributed system using load balancing with failover is one of the solutions to overcome this problem. Load balancing is a technology to divide workload among multiple servers, ensuring that no one server is overloaded. Failover is the ability to switch to a secondary system on the event of failure of the primary system. In this research, Nginx and KeepAlived are the key software packages. Nginx will be used as the load balancer, while KeepAlived will be used to configure the failover. Both methods will be implemented over the Ubuntu operating system. A number of scenarios were designed to test the designed load balancing system. Test will be conducted using JMeter software package. Based on the result of the test, the designed system was able to divided request workload among the backend and even if the load balancer server or the backend server were failing, the system was still able to keep working. Several test was also proofing that using a load balancing will decrease response time and increase the system throughput which causes an increase in the performance of the system. Based on this research, using Nginx as a load balancing combined with failover can be used as one of the solution to overcome an increasing traffic in a website.